Analysis of Creative Thinking Ability of Class X Students in Solving Biology Problems on Viruses - Maghfiroh, Nayla; Hayya, Adieba Warda (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Sukabumi, 2023)
Background: This study aims to analyze descriptively students' creative thinking skills in solving biology questions regarding viruses at class X level at MA Mazro'atul Huda Wonorenggo Demak, based on the results of written test answers given by researchers to students. Methods: The type of research is quantitative research with data in the form of numbers that are processed using simple statistical formulas. The object of this study was the 20 students in class X as a population research. Data collection techniques used were written tests, interviews, observation and documentation. The statistical analysis is simple in the form of percentage data. Results: From the analysis conducted on the creative thinking abilities of class X MIPA 1 MA Mazro'atul Huda Wonorenggo Demak, it can be concluded that students' creative thinking abilities are in the high category with a percentage of 55%. The highest percentage is in the level of detail with a percentage of 70%, while the lowest percentage is in the level of fluency and novelty with the same percentage, namely 59%. Conclusion: Students who have high level abilities are able to fulfill all categories in the indicator, students who have medium levels are able to fulfill several indicator categories, while students who have low level abilities, have not been able to fulfill all categories in indicators. Keywords : Creative thinking ability; Biology; Virus